MEKANISME PERTANGGUNGJAWABAN BADAN USAHA MILIK DESA MENURUT PERMENDES PDTT NOMOR 4 TAHUN 2015 TENTANG PENDIRIAN, PENGURUSAN DAN PENGELOLAAN DAN PEMBUBARAN BUM DESA - Aldyan Hutagalung; Mori Rajagukguk; Hisar Siregar (Visi Sosial Humaniora, 2020)
This research aims to find out how the management system of village-owned companies. Where this article refers to several rules and legislation governing the village belonging to the company. Establishment of village owned enterprises is a container that can be one of the real income sources of the coveted village can encourage the village economy to better. This business entity has a legal basis as a reference and the foundation in the implementation of its activities to run as close as possible. In the case of this writing the author uses a juridical normative research method. This approach uses approach to legislation and conceptual approach. The mechanism of accountability in conducting and carrying out the village's business activities, which is to provide a report of accountability for the implementation of the village's business activities for advisors, the village's Consultative institution is Supervisors who supervise the activities or performance of village governments, village governments must give accountability for their duties as contractors of the village-owned company to the Consultative Village agency that is submitted during village consultation.